EFFECT OF GEOMETRICAL SINGULARITY ON BUCKLING BEHAVIOR OF RECTANGULAR LAMINATED PLATES (Sciences & Technologie. B, Sciences de l'ingénieur, 2004)
In this paper, we present an analysis of a buckling behaviour of rectangular and square laminated plates with central cutouts. The laminates have in general an anisotropic behaviour, significant transverse shearing strains and a coupling between extention and bending strains. We used a four nodes shell finite element with 32 degrees of freedom. The element is based upon the Kirchhoff theory extended to the laminated structure with adoption of the equivalent mono-layer approach.A parametric study was undertaken to show the effect of certain parameters on the buckling behaviour of thin laminated plates containing square cental cutouts. The results show that the critical buckling load increases with the increase of the cutout dimension for certain boundrey conditions